Aproksymacja funkcji intensywności zgonów wielomianem trzeciego stopnia oraz metodą Gompertza-Makehama - porównanie - Gnitecka, Renata; Sipa, Magdalena (A Comparison the Approximation of the Force of Mortality with 3rd Order Polynomial and Gompertz-Makeham Formula : a Comparision, 2007)
Population mortality analysis is being carried out on the basis of the life tables. These tables include the discreet functions (e.g. death probability function) but their continuous equivalents can be approximated (e.g. the force of mortality). In the paper the approximation of the force of mortality on the basis of the data taken from the Polish life tables for men in 2004 was carried out. To do that the authors used analytical distribution of the future lifetime, Gompertz-Makeham formula and 3rd order polynomial. The authors suggested also using midpoint formula to determine the explicit form of intensity function.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 119-128